Multi-centre national audit of juvenile localised scleroderma: describing current UK practice in disease assessment and management - Hanna Lythgoe; Beverley Almeida; Joshua Bennett; Chandrika Bhat; Amarpal Bilkhu; Mary Brennan; Samundeeswari Deepak; Pamela Dawson; Despina Eleftheriou; Kathryn Harrison; Daniel Hawley; Eleanor Heaf; et al. (BMC, 2018)
Abstract Objective To describe current United Kingdom practice in assessment and management of patients with juvenile localised scleroderma (JLS) compared to Paediatric Rheumatology European Society (PRES) scleroderma working party recommendations. Methods Patients were included if they were diagnosed with JLS and were under the care of paediatric rheumatology between 04/2015-04/2016. Retrospective data was collected in eleven UK centres using a standardised proforma and collated centrally. Results 149 patients were included with a median age of 12.5 years. The outcome measures recommended by the PRES scleroderma working party were not utilised widely. The localised scleroderma cutaneous assessment tool was only used in 37.6% of patients. Screening for extracutaneous manifestations did not meet recommendations that patients with head involvement have regular screening for uveitis and baseline magnetic resonance imaging (MRI) brain: only 38.5% of these patients were ever screened for uveitis; 71.2% had a MRI brain. Systemic treatment with disease-modifying anti-rheumatic drugs (DMARDs) or biologics was widely used (96.0%). In keeping with the recommendations, 95.5% of patients were treated with methotrexate as first-line therapy. 82.6% received systemic corticosteroids and 34.2% of patients required two or more DMARDs/biologics, highlighting the significant treatment burden. Second-line treatment was mycophenolate mofetil in 89.5%. Conclusion There is wide variation in assessment and screening of patients with JLS but a consistent approach to systemic treatment within UK paediatric rheumatology. Improved awareness of PRES recommendations is required to ensure standardised care. As recommendations are based on low level evidence and consensus opinion, further studies are needed to better define outcome measures and treatment regimens for JLS.